Kesan Terapi Bermain Dulang Pasir Terhadap Konsep Kendiri Dan Kebimbangan Kanak-Kanak Yang Mengalami Penderaan - Mohd Sarji, Zahari (2020)
The purpose of this study is to examine the effectiveness of the sand tray play therapy (StPT) using the Cognitive Behavioral Therapy (CBT) approach to abused children. This study also aims to answer research question whether the case studies can support quantitative research results. Mixed method quantitative and qualitative - case study were used in the study.